Evaluation of the environmental impacts resulting from the spread of various industrial activities and fuel stations in the northwestern region of the coast extending from Tajoura in the east to Maya in the west and south to Qasr Bin-Ghashir and Al-Azeziez - salem منصور عويدات; alzarga علي عمران; Alnash عافية سالم; Sharif عمر محمد; Nassar ياسر فتحي (Journal of Pure & Applied Sciences, 2022)
Sixty samples of urban surface soil were collected to estimate the concentration of Cd, Pb, Zn, Cu, Ni, Co, Fe, Mn and Cr, and measuring some environmental pollution indices and determination of its sources. The results showed that the mean concentration of measured heavy metals is higher than permissible values set by WHO and Canadian Council of Ministers of the environment (CCME). The results of pollution indices include Single Pollution Index (PI), Contamination Factor (CF), Contamination degree index (Cdeg), Enrichment Factor (EF), Pollution Load Index (PLI), Geoaccumulation index (Igeo) are either unpolluted to moderately polluted. Whoever, Single Ecological Risk Index (SERI) and the Potential Ecological Risk Index (RI) are considered moderate environmental risks. The results of principal component analysis and factor analysis utilize to determine the sources of heavy metals in soil samples, results show the potential source of Cd, Pb, Zn, and Cu come mainly from human activities which related to industrial processes and traffic, whereas the possible source of Ni and Co could be rock components which related to soil origin materials, whereas, Cr and Cu might originate from mixed sources of natural and anthropogenic inputs. As for the Fe element, it is believed that its sole source is the geological inputs.